Opinion Analysis Based on TNF (Textual Noise Fixing) Algorithm - Ming Feng, Alen Lam; Jin Hong, Lee; Ying Ying, Soh; Omar, Abdul Halim (Multidisciplinary Applied Research and Innovation, 2022)
In today’s society, social media is widely used. Many people share their opinions or thoughts on social media, the most common is to leave a message under Facebook posts. People will vent their dissatisfaction or opinions on the government on social media. Some people will express support for the government or make some constructive suggestions on social media. During this covid issues, people will start to divide into two parts, one is in favor of the government’s approach, and the other is to start condemning the government’s approach. Our project is to collect the views and thoughts of the Malaysian people on the impact of Covid-19 on business. After the collection is complete, we will clustering it, we will divide it into two parts, one is positive and the other is negative. After the classification is completed, we will use kmean to make an output of the data.